The Use of Quizizz-Based Digital Learning Media in Increasing Interest in Learning PAI on the Topic of Deepening Faith in the Books of Allah SWT for Eighth Grade - Nandar Prasetyo Wijaya Mamonto; Razak Umar; Mariyati Podungge; Saifullah (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine the effectiveness of Quizizz-based digital learning media in increasing students’ interest in learning Islamic Religious Education (PAI) in class VIII of SMP Negeri 3 Bolaang Mongondow Utara. This research used Classroom Action Research (CAR) consisting of two cycles, namely planning, implementation, observation, and reflection. The subjects of this study were 22 class VIII students. Data collection techniques were carried out through observation, questionnaires, documentation, and learning outcome evaluations. The results showed that the use of Quizizz media was able to increase students’ learning interest significantly. Students became more active, enthusiastic, and involved during the learning process. In addition, Quizizz created an interactive and enjoyable learning atmosphere through gamification features such as leaderboard, instant feedback, and points. The percentage of students’ learning interest increased from 51.18% in cycle I to 79.22% in cycle II. Thus, Quizizz-based digital learning media can be an innovative solution in improving students’ interest in learning PAI in the digital era.